Study guides

☆☆

Q: Why is the expression 3x equivalent to the expression x plus x plus x?

Write your answer...

Submit

Still have questions?

Related questions

Radical (3x) = radical(x) * radical(3).

When x = 2, 3x + 5 = 11.

-9

It is an expression that can be simplified to 4x

The expression 3x + 5x - 8 is equivalent to 8x - 8 but, since it is not an equation (nor inequality) it cannot be solved. Consequently, x + 1 cannot be evaluated.

It is a quadratic expression and can be factored into: (3x+1)(x+2)

This expression could be reordered as 1 + 3x + 2x2.

3

Equivalent to what? "3x = 3 + x" is an equation which can be equivalent to other equations, but none is mentioned.

3x+5=14 3x=9 x=3

It depends on what it is meant to be equivalent to!

It is equivalent to: 3x+6+5 = 3x+11

It is an expression.

-3.

If you mean -3(x+10) then it is -3x-30

3(x-y)

It can also be written as 3x + 7. The value of the expression will depend on the value of x.

It is 3x-36

what is equivalent to (x plus 4)2

3x + 5 + x + 10 + 2y 4x + 2y + 15 |:2 2x + y + 7.5 2x + y + 7.5 is equivalent to the original.

x3 = x times x times x 3x = x plus x plus x

You can't simplify this expression. You can calculate a value (a number) only if you happen to know how much "x" is.

The expression does not have rational factors.

The given expression can be simplified to: x-12y

Given a value of x, find the value for -3x + 2